Propuesta de una red alternativa de movilidad interuniversidades en la ciudad de Riobamba - Caiza Valdez, Brandon Joel (2025)
The city of Riobamba faces significant mobility challenges due to the geographical dispersion of its principal educational institutions: the Regional Autonomous University of the Andes, the National University of Chimborazo, and the Polytechnic School of Chimborazo. This dispersion, combined with an inefficient public transportation infrastructure, results in prolonged commute times, traffic congestion, and considerable environmental impact. To address these issues, the implementation of a sustainable alternative mobility network is proposed. This initiative focuses on promoting environmentally friendly transportation methods and optimizing transit routes to improve inter-university connectivity and reduce reliance on private vehicles. The project is grounded in a comprehensive methodological approach that integrates both architectural and strategic planning principles to foster orderly urban development. Key components include the restructuring of existing transit routes to enhance efficiency, the incorporation of electric buses tailored to local needs, and a strong emphasis on accessibility and inclusion, ensuring that the entire university community benefits from the network. Environmental sustainability is a central priority of the proposal, aligning with global best practices in responsible urban planning. The anticipated outcomes include a substantial reduction in commute times, alleviation of traffic congestion in critical zones, and a positive environmental impact through reduced emissions. This initiative not only addresses immediate transportation concerns but also serves as a replicable model for other mid-sized cities facing similar challenges. Ultimately, it aims to promote a more sustainable, efficient, and interconnected urban future.